Commemoration, communion and courage, not celebration: Public prophetic theology 500 years after the Reformation - Kotzé, Manitza (Stellenbosch Theological Journal, 2017)
Five hundred years after the Reformation, it is tempting to celebrate this influential and significant event. The Reformation, however, as an incident which also tore apart the Church, should be commemorated, but not celebrated. What can be commended, however, is the courage shown by those involved in the Reformation, especially as seen in the figure of Martin Luther. In this contribution, I will examine the courageous voices of the Reformers, who confronted the status quo of their day in order to also draw some guidelines for a similarly courageous and prophetic theology in the present day. The concept of community and Holy Communion will especially be stressed in this regard.